Youth Subcultures in Fiction, Film and Other Media Teenage Dreams (Palgrave Studies in the History of Subcultures and Popular Music, 2018)
This collection explores the representation, articulation and construction of youth subcultures in a range of texts and contexts. It brings together scholars working in literary studies, screen studies, sociology and cultural studies whose research interests lie in the aesthetics and cultural politics of youth. It contributes to, and extends, contemporary theoretical perspectives around youth and youth cultures. Contributors examine a range of topics, including 'bad girl' fiction of the 1950s, novels by subcultural writers such as Colin MacInnes, Alex Wheatle and Courttia Newland, as well as screen representations of Mods, the 1990s Rave culture, heavy metal, and the Manchester scene. Others explore interventions into subcultural theory with respect to metal, subcultural locations, abjection, graffiti cultures, and the potential of subcultures to resist dominant power frameworks in both historical and contemporary contexts.